2012
DOI: 10.1063/1.4766519
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of BF[sub 2], Ga and In implanted Si after FLA and RTA annealing

Abstract: The dopant diffusion, electrical activation, diode I-V characteristics and damage recovery of BF 2 , Ga and In implanted Si after annealing have been investigated for samples with the peak concentration of 1.0x10 19 cm-3 as p-type dopant atoms. Within this concentration, Ga implanted samples have the low sheet resistance and lowest leakage current in diode I-V with good crystallinity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Previously, we reported [3] the dopant diffusion, electrical activation, diode characteristics and damage recovery of BF 2 , Ga and In implanted Si. Diode I-V characteristics indicated that Ga implanted Si showed the good reverse characteristics compared with other dopants.…”
Section: Introductionmentioning
confidence: 98%
“…Previously, we reported [3] the dopant diffusion, electrical activation, diode characteristics and damage recovery of BF 2 , Ga and In implanted Si. Diode I-V characteristics indicated that Ga implanted Si showed the good reverse characteristics compared with other dopants.…”
Section: Introductionmentioning
confidence: 98%